(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Aim: To Identify and characterize driveline-related injuries among patients with HeartMate II® or HeartMate 3® and assess the dressings used during hospital stay. Method: Observational, cross-sectional study conducted between 2015 and 2023 at a large hospital in São Paulo, Brazil. Results: The sample consisted of 18 patients, with driveline injuries identified in 66.7%, categorized into stages one (83.3%), two (8.3%), and four (8.3%). Of these, 66.6% were diagnosed with driveline infection according to the Utah classification: stages two (50%), three (37.5%), and four (12.5%). A correlation was found between the occurrence of injuries and longer support time (p=0.035) and the presence of a diagnosis of driveline infections (p=0.013). The solutions most frequently used were Chloraprep™ (27.8%), Aqueous Chlorhexidine 0.5% (22.2%), and Saline 0.9% (22.2%), while the dressings were IV3000™ (72.2 %), Excilon™ (44.4%), and Biatain®Ag (33.3%). Conclusion: Driveline dressings are not standardized, indicating the need for new protocols and guidelines based on studies of high methodological quality and presenting robust evidence of the best solutions and dressings to prevent complications and promote better outcomes.